The Role of Halal Task Force Unit in Ensuring Halal Products in West Kalimantan Province - Rachmawati Rachmawati; Tiza Yaniza; Uti Asikin; Ismawartati Ismawartati; Siti Rohani (PT Mattawang Mediatama Solution, 2023)
Based on Law of The Republic of Indonesia Number 33 Year 2014 concerning Halal Product Assurance, the Halal Product Guarantee Organizer (BPJPH) is one of the supporting elements in the Ministry of Religion of the Republic of Indonesia which is under and responsible to the Minister of Religion who oversees implementing halal product guarantees in accordance with the provisions of laws and regulations. BPJPH is assisted by the Halal Task Force (Satgas Halal) in carrying out its role as a halal guarantor in each region. Not spared also in the West Kalimantan area. This research is entitled The Role of the Halal Task Force (Satgas Halal) in the West Kalimantan Province Region with the aim of knowing the Role of the Halal Task Force (Satgas Halal) in Guaranteeing Halal Products in the West Kalimantan Province. The method used in this research is a juridical sociological approach method. The results of this study show that the role carried out by the Halal Product Guarantee Organizer (BPJPH) of the Ministry of Religion in Guaranteeing Halal Products in the West Kalimantan Province Region has carried out its functions, but there are still obstacles, firstly the lack of human resources, secondly a minimal budget and the third inadequate facilities and infrastructure. The efforts made by the Halal Task Force (Satgas Halal) of the Ministry of Religious Affairs, West Kalimantan Representative, to optimize product services are in synergy with all stakeholders and coordination with related agencies.